2015
DOI: 10.1074/jbc.m114.635987
|View full text |Cite
|
Sign up to set email alerts
|

Action at a Distance

Abstract: Background: COX inhibitors are classified into rapid, reversible inhibitors and slow, tight binding inhibitors. Results: Kinetics and crystal complexes of a mCOX-2 V89W mutant reveal dramatic differences in inhibitor association and dissociation. Conclusion: A mutation at position 89 efficiently converts rapid, reversible inhibitors to slow, tight binders. Significance: Kinetic and structural insights of the COX-NSAID interaction reveal a key residue at the entrance/exit of COX-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…It may be that some detergents exert an indirect effect on the cyclooxygenase channel opening that alters some structural or electrostatic interaction required for aspirin to access the cyclooxygenase channel. The altered inhibition time course of celecoxib may implicate the region around the COX-2 specific side pocket housing Arg-513 58 , although there is no precedent to suggest this residue is involved in aspirin inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that some detergents exert an indirect effect on the cyclooxygenase channel opening that alters some structural or electrostatic interaction required for aspirin to access the cyclooxygenase channel. The altered inhibition time course of celecoxib may implicate the region around the COX-2 specific side pocket housing Arg-513 58 , although there is no precedent to suggest this residue is involved in aspirin inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, ibuprofen inhibition of huCOX-1 becomes time-dependent in the presence of nonsubstrate FAs (52). Double-tryptophan murine COX-2 mutants at positions 89/90 or 89/119 enhance the time dependence of ibuprofen and mefenamic acid (65). (R)-Profens are substrate-selective inhibitors of 2-AG oxygenation by COX-2 (61).…”
Section: Time-independent Inhibitorsmentioning
confidence: 99%
“…As is seen for indomethacin, the Ser-530 hydroxyl group of COX-2 forms a hydrogen bond with the carbonyl between the indole and phenyl rings of the indomethacin moiety of compounds 1 and 2 in their respective crystal complexes. Mutation of Ser-530 to alanine decreased the potency of compound 1 (IC 50 ϭ 2.5 M) while minimally affecting the potency of com- Prior work had demonstrated that mutation of Val-89 to tryptophan alters the kinetics of inhibition of many weak reversible inhibitors so that they behave as time-dependent, tight-binding inhibitors (28). Crystal structure data revealed that the Trp-89 residue fills a gap between helixes B and D of the MBD, changing the opening of the lobby from a C-shaped partial ring to a fully closed donut shape.…”
Section: Structural Determinants Of Cox-2 Inhibition Of Compounds 1 Amentioning
confidence: 99%